Peer Review - Investigation of story ductility demands of inelastic concrete frames subjected to repeated earthquakes - Ade Faisal (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The present study focuses on the inﬂuence of repeated earthquakes on the maximum story ductility demands of three-dimensional inelastic concrete frames. A comprehensive assessment is conducted using generic frames with 3-, 6-, 12-, and 18-story structures. Each is assumed to have behaviour factors of 1.5, 2, 4, and 6 referring to Eurocode 8. Stiffness and strength degrading hysteresis rule to represent reinforced concrete structure is considered in the plastic hinge of members. Twenty ground motions are selected, and single, double, and triple events of synthetic repeated earthquakes are considered. Some interesting ﬁndings are provided showing that repeated earthquakes signiﬁcantly increase the story ductility demand of inelastic concrete frames. On average, relative increment of maximum story ductility demand is experienced 1.4 and 1.3 times when double and triple events of repeated earthquakes are induced, respectively. Empirical relationships are also provided to predict these increments where their efﬁciency is presented examining characteristic 3- and 8-story reinforced concrete buildings.